Pengembangan Mobile Learning â€œDetektif Siputâ€ Kelas X SMK - Rindiani, Rindiani; Hasanah, Fitria Nur (Universitas PGRI Semarang, 2022)
The purpose of this study was to develop and determine the feasibility of learning media, in the form of mobile learning with the name